A teleost-specific oxygen–immunity axis where FIH activates NF-κB via competitive IκBα binding - Zhipeng Zhan; Mincong Liang; Yang Yu; Yangchi Cui; Zhimin Li; Weiqiang Pan; Ziyi Zhou; Lai Jiang; Yafeng Hou; Jian He; Kun Wu; Shaoping Weng; et al. (Proceedings of the National Academy of Sciences, 2026)
Global warming–induced aquatic deoxygenation poses a severe physiological challenge to teleosts, often influencing their immune defense mechanisms. While aquatic organisms are under evolutionary pressure to balance metabolic adaptation with pathogen resistance, the molecular strategies they employ to overcome high pathogen loads under hypoxic stress remain poorly understood. Here, an oxygen–immunity regulatory axis was identified in teleosts, in which the oxygen sensor FIH (factor inhibiting HIF) activated the NF-κB pathway by competitively displacing p65 from IκBα. Experiments with FIH mutants showed that NF-κB activation did not require FIH hydroxylase activity. In vitro, FIH bound IκBα, promoted p65 nuclear translocation, and increased inflammatory gene expression. FIH knockdown blunted these responses. In vivo, CRISPR/Cas9-generated drfih –/– zebrafish showed reduced NF-κB-driven inflammation, altered responses to LPS challenge, and a dose-dependent trade-off in Vibrio anguillarum infection, with reduced resistance at a low dose but mitigated immunopathology at a high dose. AlphaFold3 modeling and mutational analyses pinpointed a competitive interface. In human cells, FIH–IκBα binding occurred without NF-κB activation. Notably, replacing a C-terminal segment of human IκBα with the teleost counterpart restored FIH-dependent competition and NF-κB activation, indicating lineage-specific structural divergence. Extensive cross-species predictions revealed that several aquatic vertebrates, an amphibian, and a shrimp species possessed a competitive interface, whereas the terrestrial species examined did not. These findings revealed a hydroxylase-independent mechanism, likely associated with aquatic lineages, that linked oxygen sensing to innate immunity and had implications for vertebrate evolution, climate-driven hypoxia, and aquaculture health.